Market chain analysis of smallholder coffee producers in debub ari district of south omo zone, SNNPR, Ethiopia - Alemayehu, Y (International Journal of Agricultural Research, Innovation and Technology, 2022)
This study mainly aimed at analyzing market chain analysis of coffee in the Debub Ari District. The descriptive and S-C-P model was used. Both primary and secondary data were collected from the study area. The multi-stage sampling technique employed for this study. A total of 194 coffee producer household heads have been randomly selected and interviewed with the help of pre-tested structured questionnaire. The focus group discussion and key informants interviews were conducted to supplement the formal data. The results of S-C-P model indicated that the four firms concentration ratio (CR4) result in the study area was found to be tight oligopolistic for both red and dry coffee which accounts 89.2 and 80.0%, respectively. About 72% of price setting was done by buyers, 27% negotiation and 1% by the producers. There are seven market channels, which have been identified in the study area. The computed marketing margin among different actors and channels indicated that the total gross marketing margin (TGMM) of coffee is high in channel I, II, III whereas the producers marketing margin (GMMp) was highest in channel VII. Therefore, the intervention is needed to improve coffee marketing chain through promoting cooperatives, infrastructural development and timely market information for efficient marketing system in the study area. Int. J. Agril. Res. Innov. Tech. 11(2): 61-68, Dec 2021